2018
DOI: 10.1002/ejp.1195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of higher versus lower threat contexts on pain‐related attention biases: An eye‐tracking study

Abstract: Through considering gaze parameters during image presentation phases of dot-probe and impending pain tasks, possible effects of lower versus higher threat contexts on attention biases were elucidated. Participants reported more fear and gazed longer at painful than neutral images in the higher threat context whereby image pairs cued possible pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 31 publications
6
16
1
Order By: Relevance
“…In this study, images were resized to 11 × 10 cm (width × height) with 100 pixels per inch and used to create 12 pain‐neutral (P‐N) face image pairs and 12 neutral‐neutral contrast (N‐Nc) face image pairs for use in both impending touch and impending pain tasks. Following related work (Jackson et al, , ), N‐Nc pairs were created by selecting 12 neutral images at random and deeming them as “Neutral‐contrast” (Nc) images, each to be paired with one of the 12 remaining neutral (N) images. Neutral image pair blocks served as fillers in each task but were included in manipulation check ratings elaborated below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, images were resized to 11 × 10 cm (width × height) with 100 pixels per inch and used to create 12 pain‐neutral (P‐N) face image pairs and 12 neutral‐neutral contrast (N‐Nc) face image pairs for use in both impending touch and impending pain tasks. Following related work (Jackson et al, , ), N‐Nc pairs were created by selecting 12 neutral images at random and deeming them as “Neutral‐contrast” (Nc) images, each to be paired with one of the 12 remaining neutral (N) images. Neutral image pair blocks served as fillers in each task but were included in manipulation check ratings elaborated below.…”
Section: Methodsmentioning
confidence: 99%
“…Empirically, initial studies based on the threat interpretation model (Sharpe et al, ; Todd, Sharpe, Colagiuri, & Khatibi, ) found neither disengagement difficulties nor speeded avoidance during prolonged presentations of pain‐neutral (P‐N) image pairs in a visual dot‐probe task that followed exposure to threatening primes about an upcoming cold pressor test. Conversely, Jackson, Su, and Wang (, ) assessed gaze biases during standardized P‐N image pair presentations whose offsets signalled (1) possible nociception from an impending pain task (higher threat context) versus (2) an absence of nociception from a dot‐probe task (lower threat context). Across healthy participants and those with chronic pain, overall gaze durations towards pain images were longer when offsets cued possible pain rather than its absence.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies featuring painful versus non‐painful images that signaled possible painful stimulation versus never painful stimulation, respectively, found biases in overall gaze durations (Jackson et al., , ) and larger LPP amplitudes (Zheng et al., ) toward (more threatening) pain images that signaled possible personal physical discomfort than (less threatening) neutral images that signaled an absence of physical discomfort. Although these studies found significant situational differences based on images that signaled possible discomfort versus its absence, none of them found trait fear of pain levels moderated overall gaze biases or late ERPs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other studies of anxiety and phobias featuring visual cues (i.e., images, words) alone, the threat value of sensory pain words versus neutral words in this study may have been compounded across FOP groups because word T A B L E 2 Mean ERP amplitudes during sensory pain word and neutral word presentations within higher versus lower trait fear of pain subgroups cues had clear implications for the relative likelihood of experiencing personal discomfort. Recent studies featuring painful versus non-painful images that signaled possible painful stimulation versus never painful stimulation, respectively, found biases in overall gaze durations (Jackson et al, 2018a(Jackson et al, , 2018b and larger LPP amplitudes (Zheng et al, 2018) toward (more threatening) pain images that signaled possible personal physical discomfort than (less threatening) neutral images that signaled an absence of physical discomfort. Although these studies found significant situational differences based on images that signaled possible discomfort versus its absence, none of them found trait fear of pain levels moderated overall gaze biases or late ERPs.…”
Section: Effects Of Fear Of Pain On Behavior and Erp Responsesmentioning
confidence: 99%
See 1 more Smart Citation